The Biographical Experience of Being a Stay-at-Home Mother of a Large Family Versus Online Activity. A Case Study - Kaźmierska, Kaja (Qualitative Sociology Review, 2025)
The article presents the analysis of two cases of women reconstructed based on autobiographical narrative interviews. They are mothers of many children and are active online, having accounts on Instagram and creating content. Most research focused on the activities of online creators is based on an analysis of their web content. Due to the type of research data, autobiographical narratives and the interpretations of one’s biographical experiences and actions are the main frame of this analysis. Both narrators represent contemporary modern women, combining opposing patterns of tradition and modernity, which are often presented in public discourses as contradictory or mutually excluding. Internet activity seems to remedy the accompanying experience of tension and supports women’s biographical work. What stands out is the identity work undertaken by the two narrators, whose frame of reference is the tension between the planned and voluntary entry into traditionally understood motherhood and the plan for one’s development inscribed in the identity of an educated modern woman socialized in a culture of individualism. In this respect, their online activity appears to have a compensatory function in their biographies.